Aktionsforschung: Expertiseforschung und forschendes Lehren und Lernen im Dualen Präsenzstudium der Sozialen Arbeit - Thorsten Sühlsen (IU Internationale Hochschule, 2022)
– The aim of this research project is to describe changes in the competence and knowledge base of prospective social workers in the course of their studies and professional activity and, if possible, to prove and link them back to questions of university professionalization in social work. What categories could be used to describe the progression of a social work degree from novice to bachelor expert? Differences between novices, bachelor experts, experts are expected in terms of the use of subject-specific skills (potentials) and skills (competencies). Methodologically, a prompting task study is conducted in an expertise research, in which experts in different fields of social work are interviewed using the method of thinking aloud. These results flow into teaching-learning-arragements, which themselves are methodically examined with video analysis and qualitative content analysis. The research and learning results from the expertise research and from the teaching-learning-arragements form a form of action research, which enables an optimal match of demand and offer of the practice locations and the university.
Keywords: 300; Aktionsforschung; Challenging situations task; Cycle of Excellence; Deliberate Practice; Expertiseforschung; Forschendes Lehren und Lernen; Forschungsmethode; Interaktionsforschung; Kompetenzforschung; Kooperatives Lernen; Lehr-Lernforschung; Prompting-Task; Reflecting Team